PENGARUH CAPITAL INTENSITY, PROFITABILITAS, DAN SALES GROWTH TERHADAP AGRESIVITAS PAJAK - Bayu Antakusuma (2021)
This study is quantitative research aimed to determine and empirically test the effect of capital intensity, profitability, and sales growth on tax aggressiveness, with leverage, firm size, and liquidity as control variables. In this study, tax aggressiveness was measured by Cash Effective Tax Rate (CETR) and Book Tax Difference (BTD). The population of this study is consumer goods companies that were listed on the Indonesia Stock Exchange (IDX). By using the purposive sampling method, the total sample obtained was 76 consumer goods companies during the 2017-2019 period. The data analysis technique used in this study is multiple linear regression with the STATA v.16 program. The results of this study indicate: 1) capital intensity has a positive and significant effect on tax aggressiveness with the BTD measurement but does not affect tax aggressiveness with the CETR measurement. 2) profitability has a positive and significant effect on tax aggressiveness. 3) sales growth has a positive and significant effect on tax aggressiveness.